PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN GRESIK - WAHYU DWI KURNIAWAN (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The purpose of this study is to find out the work discipline, work motivation and work environment on the performance of employees in the financial management and gresik district asset management agencies. The sample uses probability sampling technique as many as 72 respondents propotionate stratified random sampling. Data analysis techniques using multiple linear regression. The results of multiple linear regression analysis prove that work discipline, work motivation and work environment are proven to have a significant partial effect on employee performance in financial management and gresik district assets. Simultaneously work discipline, work motivation and work environment also proved to have a significant effect on performance